2010
DOI: 10.1111/j.1365-3032.2010.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Territorial damselflies do not show immunological priming in the wild

Abstract: Adaptive immunity allows vertebrates to gain protection against repeated pathogenic infections. Analogous responses (priming) have been recently uncovered in invertebrates. However, whether such responses are widespread is not known. The present study investigated the presence of immunological priming in males of a species whose phylogenetic position places it in one of the less derived insect orders. It is hypothesized that the efficiency of such a response could be related to animal condition, as assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Immune priming decreases susceptibility of some arthropods to some pathogens [35,10,31,32], but it is not universal to all insect-pathogen interactions [33,34]. Here, we saw no evidence of pre-exposure to bacterial elicitors impacting survival against two bacterial pathogens, even when, in the case of E.…”
Section: Discussionmentioning
confidence: 61%
“…Immune priming decreases susceptibility of some arthropods to some pathogens [35,10,31,32], but it is not universal to all insect-pathogen interactions [33,34]. Here, we saw no evidence of pre-exposure to bacterial elicitors impacting survival against two bacterial pathogens, even when, in the case of E.…”
Section: Discussionmentioning
confidence: 61%
“…Other studies have found no evidence for priming at all [58]–[60]. Priming can also be variable within a host-parasite system, suggesting it may sometimes be context dependent [10], [61].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that immune priming occurs because the insect is inherently able to activate immune responses more rapidly during a second exposure, or because pathogens or pathogen components are retained within the insect, which maintains the animal in a heightened state of immune alertness (Masri and Cremer, 2014). Although immune priming has been demonstrated in multiple insect orders, it is not a universal feature of the insect immune system, nor is it universal for all infection types (Gonzalez-Tokman et al, 2010; Reber and Chapuisat, 2012). …”
Section: Immune Primingmentioning
confidence: 99%